Spatio-temporal changes analysis (1984-2017) of a grazed Cretan landscape using Landsat satellite images - Chouvardas D.; Kourakli P.; Kalaitzidis C.; Kazakis G.; Karatassiou M. (Pastoralism and sustainable development: proceedings, 2021)
Research on spatio-temporal changes on grazed landscapes of Greece in general and of Crete specifically, indicates that forests, as in all Mediterranean, are expanding. Nowadays, such studies often use digital image analysis methods applied on multispectral satellite images. The recent open access availability of ground reflectance products derived from historical Landsat imagery, which have been geometrical and atmospheric corrected, is expected to increase their use for land use/land cover change research. The aim of this paper was to study the spatio-temporal changes of a typical Cretan landscape (Municipality of Sfakia) and to test the efficiency of the recently available Landsat products, for these purposes. Landsat images of 1984, 2001 and 2017 were processed by classification techniques using remote sensing and GIS software. Forest orthophoto maps and relevant inventory data were also collected, and landscape metrics were calculated. Data analysis of spatio-temporal changes showed a gradual expansion in size and density of forest in silvopastoral areas and of silvopastoral areas in phrygana, increasing landscape heterogeneity. The abandonment of marginal agricultural areas, in combination with the reduction of wood harvesting, are the most important factors of landscape changes in relation to animal husbandry evolution. If this trend continues, it is possible for this Cretan landscape to degrade.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)